Influence of tidal mixing on bottom circulation in the Caroline Sea - Wang, Xiaowei; Liu, Chuanyu; Wang, Fan (Frontiers in Marine Science, 2024)
By use of a high-resolution regional ocean model, the influence of tidal mixing processes on bottom water and circulation in the Caroline Sea is investigated. Based on different configurations for diapycnal diffusivities of tidal mixing, three numerical experiments are performed: one completely without tidal mixing, one only with local tidal mixing due to the locally dissipated tidal energy, and one considering tidal mixing processes induced by the total dissipated tidal energy. The results show that tidal mixing processes in the abyssal Caroline Sea could sustain a relatively high horizontal density gradient and hence baroclinic pressure gradient not only across the two deep-water passages connecting to the open ocean, but also within the abyssal West Caroline Basin (WCB) and East Caroline Basin (ECB). Therefore, tidal mixing processes could maintain the large amounts of bottom water inflow, intensify the bottom basin/subbasin-scale horizontal circulation, and drive a more vigorous meridional overturning circulation in the abyssal WCB and ECB. Moreover, simulations of bottom water transport in the experiment with tidal mixing processes are more consistent with previous observations and estimates. These results suggest that tidal mixing processes plays a crucial dynamic role in the bottom circulation, and is essential for ocean modelling.